The Logic of State Authority on the Control of Agrarian Resource (Socio-Anthropological and Islamic Perspective) - Jamrozi, Ahmad Syafi’i Sulaiman; Lukito, Ratno (American Journal of Social Sciences and Humanities, 2019)
The development of property right to land, in its historical trajectory, has shown a fairly dynamic development. In the Indonesian context, the dynamics, at least seen in the diverse conceptions of the state’s rights of control over the land from the colonial era with its Domein Verklaring up to the national era with its State’s Right of Control. This paper aims to examine issues of legitimacy and authority of state control over land. By using socio-anthropological approach and Islamic law perspective, this study shows that although the logic of the state authority in land tenure takes place dynamically, the existence of indigenous peoples with their customary law and ulayat rights basically has not experienced significant process of change, even though the ruler and political law are different. Both of these concepts in the realm of practice appear to equally place the indigenous peoples following their customary rights in marginalized positions.